Evaluation of the Contribution of UNDP Global and Regional Human Development Reports to the Public Policy Process - United Nations Development Programme (United Nations, 2015)
The Evaluation of the Contribution of UNDP Global and Regional Human Development Reports (HDRs) to the Public Policy Process is an independent thematic evaluation conducted by the Independent Evaluation Office (IEO) of the United Nations Development Programme (UNDP) in 2014. It assesses the contribution of global and regional HDRs to public policy and policy discourse from 2004 to 2013. This is the first independent evaluation of the global and regional HDRs, so the evaluation also considers the way that HDRs progressed from 1990 to 2003. UNDP’s Executive Board approved this evaluation, taking particular note of the HDRs’ important advocacy role in promoting the human development perspective in development policy and planning. In addition to accountability and learning objectives, the evaluation focuses attention on the public policy and pedagogical value of these flagship UNDP knowledge products